Effect of Temperature and Holding Time Variations in the Annealing Process of Ni-Hard Material on Machinability - Antonius Adi Soetopo; Reza Yadi Hidayat; Billy Heriawan; Dede Buchori Muslim; Paulus Mudji (Postgraduate, University of Mataram, 2025)
Ni-Hard cast iron was selected for the pump cover material because of its exceptional abrasion resistance afforded by a Ni–Cr-alloyed, martensitic matrix with hard carbides. This alloy (e.g. ASTM A532 Ni-Hard 4) typically has hardness in the 50–58 HRC range. However, this extreme hardness makes conventional machining difficult, often causing rapid tool wear and poor surface finish. In contrast, conventional cast irons like FC25 machine easily but fail prematurely under abrasive service. Thus, to balance wear resistance and machinability, we heat-treated Ni-Hard. Annealing experiments (400–600 °C and 800–1000 °C) were carried out, followed by hardness testing and machining trials. We find that high-temperature annealing (1000 °C, 4–6 h) effectively softens the Ni-Hard (to 39–32 HRC), enabling conventional milling with minimal tool failure. Lower-temperature anneals produced little softening and even carbide precipitation. These results agree with literature on high-Cr iron annealing. The softened microstructure (spheroidized carbides, ferrite/austenite matrix) and substantially improved machinability validate Ni-Hard’s suitability after annealing for abrasive slurry pump components.